Profil Perilaku Narsisme Remaja serta Implikasinya Bagi Bimbingan dan Konseling - Wida Widiyanti; M Solehuddin; Aas Saomah (Indonesian Journal of Educational Counseling, 2017)
The behavior of narcissism on adolescent became one of some focuses by teachers of Guidance and Counseling to more comprehend the problem of students. The approach of Freudian traditional psychodynamic put narcissism as a failure of running progress passing through lower level in psychosexual development. The research is aimed to know general description of student narcissism in adolescence. The approach that was used in this research is quantitative approach where the research method is descriptive method. The result of research showed that generally narcissism level of students is categorized average, where it was obtained by data collection tool exactly using questionnaire narcissism behavior that were scattered randomly to students grade VIII SMP Negeri 29 Bandung year 2015/2016. Based on the research result, some student was found in high category, it means that should to hand over the case to the expert who can help more accurate. Meanwhile, some students who are in average and low category need some guidance service for preventing narcissism behavior that psychologically disrupt them.